The Influence of Digital Queue Service Quality on Patient Waiting Time Efficiency at the Polyclinic of TK.IV 01.07.02 Binjai Hospital in 2025 - Normalini Potu; Felix Kasim; Sri Melda Br Bangun (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2026)
Queues occur when service demand exceeds facility capacity, causing patients to wait to receive care. Previous studies have shown that the implementation of a digital queuing system can reduce patient waiting times and improve efficiency as well as satisfaction with hospital services. This study aimed to analyze the effect of digital queuing service quality on the efficiency of patient waiting times at TK.IV 01.07.02 Binjai Hospital in 2025. This research used a quantitative method with a cross-sectional design. Sampling was conducted using the accidental sampling method. The sample in this study consisted of 113 patients who visited TK.IV 01.07.02 Binjai Hospital. The study was carried out at TK.IV 01.07.02 Binjai Hospital. The results showed that all dimensions of digital queuing service quality namely tangibles, reliability, responsiveness, assurance, and Empathy had a significant effect on the efficiency of patient waiting times at TK.IV 01.07.02 Binjai Hospital in 2025 (p < 0.05). The tangibles aspect, such as the comfort of waiting rooms and digital facilities, helped accelerate service processes, while reliability and responsiveness improved the accuracy and speed of the system and staff in handling patients. The assurance aspect fostered patients’ sense of safety and trust in staff professionalism, while Empathy encouraged humane communication and facilitated smoother service flow.Overall, improvements in all five aspects were proven to shorten waiting times and enhance service efficiency in hospital outpatient clinics. The conclusion of this study is that all dimensions of digital queuing service quality reliability, responsiveness, assurance, and Empathy significantly affect the efficiency of patient waiting times at the hospital. Among the five aspects, Empathy was identified as the most dominant factor in improving the efficiency of patient waiting times.